2007
DOI: 10.1212/01.wnl.0000267338.45673.f4
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic pitfalls in sporadic transthyretin familial amyloid polyneuropathy (TTR-FAP)

Abstract: Transthyretin familial amyloid polyneuropathies (TTR-FAPs) are autosomal dominant neuropathies of fatal outcome within 10 years after inaugural symptoms. Late diagnosis in patients who present as nonfamilial cases delays adequate management and genetic counseling. Clinical data of the 90 patients who presented as nonfamilial cases of the 300 patients of our cohort of patients with TTR-FAP were reviewed. They were 21 women and 69 men with a mean age at onset of 61 (extremes: 38 to 78 years) and 17 different mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
160
1
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(181 citation statements)
references
References 15 publications
10
160
1
10
Order By: Relevance
“…Misleading CIDP presentations have been occasionally reported in TTR‐FAP14, 38; we found 20% of our cohort of French ancestry fulfilling CIDP criteria. This is to our knowledge the first study able to estimate the prevalence of pseudo‐CIDP presentation in a large cohort of non‐Portuguese FAP patients.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Misleading CIDP presentations have been occasionally reported in TTR‐FAP14, 38; we found 20% of our cohort of French ancestry fulfilling CIDP criteria. This is to our knowledge the first study able to estimate the prevalence of pseudo‐CIDP presentation in a large cohort of non‐Portuguese FAP patients.…”
Section: Discussionsupporting
confidence: 47%
“…LateMet30 accounts for 40% of cases. The remaining patients carry 1 of the 29 known TTR mutations in France,13 leading to different patterns of neuropathy 14…”
mentioning
confidence: 99%
“…Unfortunately, we were not able to test the entire family in order to clarify this point. Recently, Plantée-Bordeneuve et al 10 demonstrated that sporadic cases are prone to late diagnosis and its deleterious consequences, like inappropriate treatments Our data emphasize the importance of performing nerve biopsy in atypical or unresponsive CIDP cases, and of sequencing the TTR gene if an amyloid infiltrate is found or if there are significant small nerve fiber manifestations, even in the absence of a positive family history 10 .…”
Section: Discussionmentioning
confidence: 66%
“…The demyelinating feature suggested by NCS has been reported as the most common pitfall in diagnosing sporadic cases of FAP (10), and in some late-onset FAP patients with ATTR V30M, the slowing of conduction velocity and prolongation of distal latency were reported to be conspicuous (11). In fact, the electrophysiological findings of the right ulnar nerve observed in our patient also hampered the correct diagnosis in our patient.…”
Section: Discussionmentioning
confidence: 57%